PROBLEMATIKA SUPERVISI PENDIDIKAN DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SDN 001/XI SUNGAI PENUH - Monalisa; Sakini Putri Sindayani; Mhd. Kurniawan; Wisnarni (STKIP Subang, 2026)
Educational supervision plays an important role in improving the quality of learning in schools. Effective supervision enables teachers to enhance their pedagogical competence and improve classroom instructional practices. However, in practice, the implementation of academic supervision often encounters various challenges related to management, teacher readiness, and the follow-up process after supervision activities. This study aims to analyze the problems of educational supervision in improving the quality of learning at SDN 001/XI Sungai Penuh and to identify strategies for strengthening academic supervision in elementary schools. The research employed a qualitative descriptive approach with a case study design. Data were collected through classroom observations, in-depth interviews, and documentation involving the school principal and teachers. The data analysis technique used an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that academic supervision contributes significantly to improving the quality of learning through the enhancement of teachers’ pedagogical competence, the development of innovative teaching practices, and the strengthening of teachers’ professional reflection. However, several challenges remain, including limited supervision time, high administrative workloads for teachers and principals, varying levels of teacher readiness, perceptions of supervision as merely evaluative, and the lack of structured follow-up programs after supervision activities. Therefore, this study recommends the implementation of collaborative supervision, strengthening teacher learning communities, and utilizing technology in the supervision process to enhance the effectiveness of educational supervision in elementary schools.